2020
DOI: 10.3390/pathogens9070550
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds from the Marine Brown Alga Caulocystis cephalornithos with Potent In Vitro-Activity against the Parasitic Nematode Haemonchus contortus

Abstract: Eight secondary metabolites (1 to 8) were isolated from a marine sponge, a marine alga and three terrestrial plants collected in Australia and subsequently chemically characterised. Here, these natural product-derived compounds were screened for in vitro-anthelmintic activity against the larvae and adult stages of Haemonchus contortus (barber’s pole worm)—a highly pathogenic parasitic nematode of ruminants. Using an optimised, whole-organism screening system, compounds were tested on exsheathed third-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…Both compounds 1 and 2 induced a Ski phenotype in 50% and 28% of in vitro-raised L4s (Table 1), with IC 50 values of 31 and 62 µM, respectively. This phenotype has previously been associated with damage of subcuticular musculature and mitochondria [15]. In addition, all L4s exposed to 100 µM of 1 exhibited marked destruction of somatic (gut and muscle) cells and tissue disintegration (Figure 3).…”
Section: Biological Evaluation Of Dysidenin (1) and Dysideathiazole (...supporting
confidence: 51%
“…Both compounds 1 and 2 induced a Ski phenotype in 50% and 28% of in vitro-raised L4s (Table 1), with IC 50 values of 31 and 62 µM, respectively. This phenotype has previously been associated with damage of subcuticular musculature and mitochondria [15]. In addition, all L4s exposed to 100 µM of 1 exhibited marked destruction of somatic (gut and muscle) cells and tissue disintegration (Figure 3).…”
Section: Biological Evaluation Of Dysidenin (1) and Dysideathiazole (...supporting
confidence: 51%
“…While none of the fractions were active against H. contortus xL3 motility and development, fractions F52 and F53 induced an abnormal skinny ( Ski ) phenotype in 45.4% and 66.6% of developing larvae, respectively, on day 7 (Figure ). Larvae with the Ski phenotype have a reduced width and a shrivelled, dehydrated appearance, as previously described, , with reference to the untreated control. Additionally, a newly identified vacuolar ( Vac ) phenotype was displayed in L4s treated with F52 (2.5%) at day 7; this phenotype exhibited major damage to various tissues in the L4 stage (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…445 In 1980 researchers from the Roche Research Institute for Marine Pharmacology reported 6-tridecylsalicylic acid (7.93) as the anti-inammatory principle from a southern Australian (Victorian) collection of the brown alga Caulocystis cephalornithos, 446 while a subsequent 2006 analysis of Tasmanian samples of C. cephalornithos reported the major metabolites as 7.93 and 6-undecylsalicylic acid (7.94), with trace amounts of the 6-dodecyl, 6-tetradecyl and 6-pentadecyl homologues. 447 In 2020, 448 7.93 and 7.94 were re-isolated from southern Australian (Victorian) collections of C. cephalornithos, as inhibitors of H. contortus L4 larvae motility, 7.93 (EC 65 29 mg mL −1 aer 72 h) and 7.94 (EC 46 29 mg mL −1 aer 72 h), with both inducing a distinctive skinny-straight (Sks) phenotype with substantial subcuticular tissue destruction (>90% aer 72 h). Interestingly, two reports in 2017 revealed 7.93 and 7.94 as rst-in-class small molecule inhibitors of the transcription factor SOX18, leading to the development of a new small molecule treatment for breast cancer and for the suppression of cancer metastatic spread.…”
Section: Brown Algaementioning
confidence: 99%